Self-sampling for high-risk human papillomavirus as a follow-up alternative after treatment of high-grade cervical intraepithelial neoplasia - Östensson, Ellinor (Oncol Lett, 2021)
Women treated for high-grade cervical-intraepithelial-neoplasia (CIN) require long-term follow-up with high-risk human-papillomavirus (HPV) testing. Self-sampling for HPV is well-accepted among these patients, but its role in follow-up for this group requires investigation. The present study examined how well HPV findings from self-sampled vaginal (VSS) and urine specimens correctly identified women from this cohort with recurrent CIN2+ compared with samples collected by clinicians. At 1st post-conization follow-up, 531 patients (99.8% participation) gave urine samples, performed VSS, underwent colposcopy with punch biopsy of visible lesions and clinician-collected cervical sampling for HPV analysis and liquid-based cytology. A total of 113 patients with positive HPV and/or abnormal cytology at 1st follow-up underwent 2nd follow-up. At 1st follow-up, all patients with recurrent CIN3 had positive HPV results by all methods. Clinician sampling and VSS revealed HPV16 positivity in 50% of recurrent cases and urine sampling revealed HPV16 positivity in 25% of recurrent cases. At 2nd follow-up, all 7 newly-detected CIN2/3 recurrences were associated with HPV positivity on VSS and clinician-samples. Only clinician-collected samples detected HPV positivity for two adenocarcinoma-in-situ recurrences, and both were HPV18 positive. A total of 77 patients had abnormal cytology at 1st follow-up, for which HPV positivity via VSS yielded highest sensitivity. The HPV findings were positive from VSS in 12 patients with high-grade squamous-intraepithelial-lesions (HSIL), and 11 patients with HSIL had positive HPV findings in clinician-collected and urine samples. All methods for assessing HPV presence yielded significant age-adjusted odds ratios for predicting abnormal lesions at 1st follow-up. For overall HPV results, Cohen's kappa revealed substantial agreement between VSS and clinician sampling, and moderate agreement between urine and clinician sampling. Clinician sampling and VSS were highly concordant for HPV16. Insofar as the pathology was squamous (not glandular), VSS appeared as sensitive as clinician sampling for HPV in predicting outcome among the present cohort. Since VSS can be performed at home, this option can maximize participation in the required long-term follow-up for these women at high-risk.